Sosialisasi Upaya Preventif Penyebaran Coronavirus Disease 2019 (COVID) di SMAN 15 Muaro Jambi - Hendra Dhermawan Sitanggang; Ummi Kalsum; Evy Wisudariani (Prodi Ilmu Kesehatan Masyarakat, FKIK Universitas Jambi, 2022)
Coronavirus Disease 2019 (COVID-19) is still a global public health problem. However, Indonesia has decided to conduct Face-to-face Learning in the learning process. Schools need to implement strict health protocols to prevent the spread of COVID-19 in the school. Schools (teachers and education personnel) have an essential role in monitoring and ensuring the implementation of health protocols. Therefore, socialization about preventing the spread of Coronavirus Disease 2019 (COVID-19) must be done at SMAN 15 Muaro Jambi Regency. The target of the socialization was teachers and education staff at SMAN 15 Muaro Jambi Regency. The Pondok Meja Health Center and the community service team delivered the socialization material using lecture and discussion methods. This activity also measures knowledge before and after socialization. Data were analyzed univariate and bivariate using the Wilcoxon test. Seventeen teachers and education staff attended the socialization activity. The results showed that respondents' average level of knowledge before socialization was 7.94, with a standard deviation of 0.899, and after socialization was 8.35, with a standard deviation of 1.455. The Wilcoxon test showed no difference in the respondents' knowledge before and after socialization. However, there was an increase in the average level of knowledge before and after, from 7.94 to 8.35. Through this socialization, it is hoped that schools can improve the implementation of COVID-19 prevention efforts in schools during face-to-face learning.Keywords: COVID-19, prevention, school, socialization